Role of Ayurveda in Enhancement of Mobility and Muscle Strength of the Elderly – A Review - Kaushik, Jyoti (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Aging is associated with several diseases, which are mainly due to the depletion of physiological reserves and the weakening of the immune mechanism. People’s quality of life is reduced by many health problems such as pain, fatigue, and mobility impairments. Decreased mobility and decreased muscle strength end up with multiple medications without complete treatment, leading to the deterioration of a person’s physical and mental health. Ayurveda primarily focuses on maintaining general health by preventing the entry of disease-causing substances to keep a person healthy. India is only the second country with the largest elderly population in the world after China. Ayurveda offers a wide range of preventive measures to combat the aging process. It has a focused branch called Rasayana, Panchakarma therapy which mostly treats geriatric problems. Various Panchakarma therapies, such as Abhayanga, Shastika Shali Pinda Sweda, Janu Basti, and Kati Basti aim to improve a person’s mobility and muscle strength. In spite, of this regular Yoga and Pranayama, Lifestyle modifications can help improve muscle strength in old age. Aim: The aim of the study is to find out Ayurvedic principles significant in the enhancement of mobility and muscle strength in old age peoples. Material and Methods: Systematic data from various journals, text books, and published articles are collected. Conclusion: Ayurvedic therapies, such as panchakarma and rasayana chikitsa, and lifestyle modifications, work synergistically to improve physical functions and vitality. Integrating Ayurveda with conventional geriatric care provides a comprehensive strategy to address the multifaceted challenges of aging.